The Yale Swallow Protocol An Evidence-Based Approach to Decision Making - Leder, Steven B.; Suiter, Debra M. (Springer International Publishing : Imprint: Springer, 2014)
The Yale Swallow Protocol is an evidence-based protocol that is the only screening instrument that both identifies aspiration risk and, when passed, is able to recommend specific oral diets without the need for further instrumental dysphagia testing. Based upon research by Drs. Steven B. Leder and Debra M. Suiter, an easily administered, reliable, and validated swallow screening protocol was developed and can be used by speech-language pathologists, nurses, otolaryngologists, oncologists, neurologists, intensivists, and physicians assistants. In addition, the protocol can be used in a variety of environments, including acute care, rehabilitation, and nursing homes. The Yale Swallow Protocol meets all of the criteria necessary for a successful screening test, including being simple to administer, cross-disciplinary, cost effective, acceptable to patients, and able to identify the target attribute by giving a positive finding when aspiration risk is present and a negative finding when aspiration risk is absent. Additionally, early and accurate identification of aspiration risk can significantly reduce health-care costs associated with recognized prandial aspiration.